Comparison of contrasting gold mine processing residues in a temperate rain forest, New Zealand. (September 2017) - Malloch, Kirstine R.; Craw, Dave
Abstract: Processing residues high in metallic elements are the legacy of historic gold processing sites, concentrating naturally occurring metalloids in the ore (As, Sb) as well as chemicals and metals added during processing to recover the gold (Zn, Pb, Hg). This study uses electron microscopy to investigate the link between variations in processing residue mineralogy and the processing technique used to extract the gold. Semi-cemented amorphous ferric arsenate and As-bearing iron oxyhydroxides attenuating As, Zn and Pb are the products of the simplest processing technique of crushing, sulphide concentration and gold recovery through Hg-amalgamation. Zinc, Pb and Ca added during cyanidation form Zn-rich carbonate and Zn oxide mineralogy. Ore roasting concentrates As to elevated levels (>35 wt%) as well as concentrating Sb from the ore, and Hg from the amalgamation process. Roasting rapidly oxidises sulphide concentrates producing toxic and highly mobile arsenolite (As2 O3 (As 3+ )). Roaster tailings processed by all of these techniques, crushing, roasting and cyanidation, are largely comprised of As-hematite and quartz. Mine residue weathering causes localised acidification and leaching of metallic elements, along with the high rainfall on these site remobilising elements. Lime added during processing and the carbonate-host rock neutralises this acidification. The formation of secondary Fe 3+ oxyhydroxide minerals formed during residue weathering and oxidisation sequesters As, Zn and Pb. Redox conditions and the pH of a site will control the stability of these secondary minerals. The toxicity of a site/processing residue can be correlated to the processing technique used, with characterisation of processing residue mineralogy having important implications for site remediation and management. Highlights: Ore mineralogy (As, Sb) and processing techniques determines element concentrations. Zn, Pb, Hg added to aid gold recovery are concentrated during processing. Ore roasting produces highest As, concentrates Hg from amalgamation. Oxidation of mine residues forms secondary Fe III -rich minerals, attenuates As, Pb, Zn. Secondary mineral stability controlled by site redox and pH conditions.